(3cJGH aj GdJUhas - (3eLghds
(3ChdgG (B:s
.. (3GdJcGaD aj GdOjf hGdYbd hGdMQjI hEecGf GSJjaGA JhLH GdbUGU EdG Cf jUWdMG Ydi GdOjI Ch jYah Gdhdj Gh jchf GdLGfj CHG ddeLfj Ydjg heY YOe GdTQhW hGdTHg Hg jhLH GdqOjI aj eGd GdLGfj hGdNWC GdeMV aj eGd YGbdJg (B...s
(3BNQgG (B:s
.. (3aeG YOG GdUhQI GdChdi hYdi bhd LeGYI ajgG CjVG HbGYOI GdVejeI NdGaG ddJPcQI ajHWd ddLgGdI hdhe JDHQ GdfNdI hHjYJ aGdWdY ddeTJQj HdG NdGa aJhi hfUG hgd jNJU Pdc (B....s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs